Diplomasi Pertahanan Di Laut Cina Selatan: Solusi Strategis (Defense Diplomacy in the South China Sea: Strategic Solution) - Prayoga, Adhit; Astika, I Putu; Surya, Krisna; Sani, Pipit Aryati (Universitas Perrtahanan Indonesia (UNHAN), 2021)
China's reclamation and infrastructure development in the South China Sea area poses a threat to countries around the region, including Malaysia. China also carried out illegal actions that violated state borders around the South China Sea, one of which was the maneuver of the Chinese air force inside Malaysia's sovereign territory on June 1, 2021. One of Malaysia's steps in dealing with this problem is to use defense diplomacy efforts, both bilateral and multilateral. Bilaterally, Malaysia can cooperate with Vietnam to strengthen maritime security, which is expected to be potential bilateral cooperation to reduce disputed claims in the South China Sea. Meanwhile, within the framework of multilateral cooperation, Malaysia can maximize existing cooperation forums such as through the ASEAN Regional Forum (ARF), ASEAN Plus Three (APT), East Asia Summit (EAS), ASEAN Defense Ministers' Meeting (ADMM), and ADMM-Plus. In dealing with problems in the South China Sea region, Malaysia has the pillars of a national defense strategy, namely concentric deterrence, comprehensive defense, and credible partnerships.